Decay resistance and dimensional stability of Araucaria angustifolia using siloxanes synthesized by sol-gel process - Giudice, Carlos Alberto (2013)
Solid wood specimens of Araucaria angustifolia were impregnated with alkoxysilanes hydrolyzed and condensed “in situ” by the sol–gel process. Alkoxysilanes selected were aminopropyl methyldiethoxysilane and aminopropyl triethoxysilane; it was also used the aminopropyl methyldiethoxysilane/aminopropyl triethoxysilane mixture in 50/50 ratio w/w. The pH was adjusted to alkaline value for controlling kinetic of hydrolysis and condensation reactions. Impregnation process was carried out under controlled operating conditions to achieve different weight gains of the chemical modifier. Unmodified and modified wood specimens were exposed to brown rot (Polyporus meliae) and white rot (Coriolus versicolor) under laboratory conditions. The results indicate that the improved resistance to fungal exposure would be based on the wood chemical modification (the protection of cellulose caused by steric hindrance of ≡Si–O–Cellulose preventing the formation of enzyme–substrate complex). Moreover, the results also would be based on the enhanced dimensional stability of the treated wood; the quoted high dimensional stability, which limits the growth of the spores, is supported in the hydrophobicity generated by both the decreasing of the amount of polar hydroxyl groups and the partial occupation of pores with polysiloxanes.